Do we still operate on the same patients for cardiac myxoma? 30-year experience of a single cardiac surgical centre - Perek, Bartłomiej; Misterski, Marcin; Stefaniak, Sebastian; Sarnowski, Wojciech; Stachowiak, Wojciech; Buczkowski, Piotr; Ligowski, Marcin; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Aim : To assess a clinical profile of patients who have undergone an operation for cardiac myxoma for 30 years in a single cardiac surgical centre. Material and methods : The study involved 64 patients (42 women and 22 men) at the mean age of 51.4 ±15.0 years. Patients were divided retrospectively into three subgroups: A – patients treated in the years 1981-2000 (n = 23), B – in the years 2001-2006 (n = 21) and C – between 2007 and 2009 (n = 20). The age of the patient, predominant clinical symptom, period between onset of symptoms and diagnosis, functional status and prevalence of the concomitant disorders were analyzed. Results : In the years 1981-2000, operated subjects (mean age of 44.7 ±13.5 years) were significantly (p < 0.001) younger than in the following years (55.2 ±12.4 and 63.7 ±12.9 years; in group B and C, respectively). Before surgery, in group A more than 60% were found in NYHA classes III and IV while in group C only 25%. The period between onset of symptoms and final diagnosis was 75 ±18 days in group A, 56 ±16 days in group B and only 23 ±7 days in group C (p < 0.001). Nobody in group A required coronary artery bypass grafting but 4 individuals in group C (20%) did. Conclusions: Retrospective analysis of a group of patients with benign cardiac tumour revealed that the profile of operated subjects had been changed. Nowadays patients undergoing surgery are older with more concomitant cardiovascular pathologies. Recently, a period between symptoms onset and surgery has been shortened.